Catalytic deoxygenation of fatty acidsviaketonization and _-carbon scissions over layered alkali titanate catalysts under N2 - Tosapol Maluangnont; Piyasan Praserthdam; Tawan Sooknoi (My University, 2022)
The palmitic acid conversion and products selectivity correlate to the partial charge at the O-atom of the lepidocrocite-type layered alkali titanate catalysts.
Keywords: Deoxygenation; Lepidocrocite; Carbon fibers; Catalysis and Hydrodesulfurization Studies